Changes in the recreational physical activity (RPA) behaviours caused by COVID-19 lockdown - a case study of Poland - Kantyka, Joanna; Maciąg, Justyna; Herman, Damian (Leisure studies, 2023)
This article aims to describe, explain and compare the changes in Poles' recreational physical activity (RPA) behaviours that emerged in response to the restrictions introduced by the Covid-19 pandemic. The literature review revealed gaps regarding this subject. Of particular interest is taking into account the comparison of both the national and international context and the comprehensive approach to explaining the mechanism of change. Based on the literature, the theoretical framework was developed, which was then used to design an online questionnaire. The questionnaire was conducted from 20 May to 31 October 2020 and included 533 respondents. To analyse the data, a combination of quantitative and qualitative analysis methods was used (descriptive statistics and grounded theory techniques). Research has shown that RPA behaviours changed temporally or permanently. The behaviours were partially differentiated by gender and age. In comparison to other countries, it seems to be a result of the range and strictness of the introduced restrictions and national culture. The novelty of the work consists of the combined data analysis methods, which allow for an explanation of the mechanism of changes and a comparison of results with other countries.